2009
DOI: 10.1007/s11740-009-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Taguchi’s optimization of process parameters for production accuracy in ultrasonic drilling of engineering ceramics

Abstract: This paper presents a study of the effect of process parameters on production accuracy obtained through ultrasonic drilling of holes in alumina based ceramics using silicon carbide abrasive. Production accuracy in ultrasonic drilling involves both dimensional accuracy (hole oversize) and form accuracy (out-ofroundness and conicity). The parameters considered are workpiece material, tool material, grit size of the abrasive, power rating and slurry concentration. Taguchi's optimization approach is used to obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 14 publications
1
19
0
Order By: Relevance
“…The response surface methodology (RSM) and Taguchi techniques for design of experiments seem to be the most wide-spread methodologies for the surface roughness prediction problem. Jadoun et al [1] employed Taguchi method to investigate the effect of some process parameters on tool wear and production accuracy in ultrasonic drilling of holes on alumina based ceramics. Some researchers [2,3] investigated the influence of various operating parameters on material removal rate (MRR), surface quality, and other characteristics on USM of engineering materials.…”
Section: Introductionmentioning
confidence: 99%
“…The response surface methodology (RSM) and Taguchi techniques for design of experiments seem to be the most wide-spread methodologies for the surface roughness prediction problem. Jadoun et al [1] employed Taguchi method to investigate the effect of some process parameters on tool wear and production accuracy in ultrasonic drilling of holes on alumina based ceramics. Some researchers [2,3] investigated the influence of various operating parameters on material removal rate (MRR), surface quality, and other characteristics on USM of engineering materials.…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of a Taguchi method-based model was adopted for developing a mathematical formulation of SR using Buckingham's p-theorem. Jadoun et al [8] applied Taguchi method for identifying the optimal settings for workpiece material, tool material, grit size of the abrasive, power rating and slurry concentration of an USM process. The effects of those process parameters on oversize, out-of-roundness and conicity were also studied.…”
Section: Literature Reviewmentioning
confidence: 99%
“…, and Jadoun et al (2009) have observed multiple responses while studying the USM processes. However, they have attempted to determine the optimal process conditions separately for different responses.…”
Section: Introductionmentioning
confidence: 99%
“…have determined the optimal conditions for MRR, TWR and SR separately. Jadoun et al (2009) have carried out a study on ultrasonic drilling of engineering ceramics and observed three performance measures, e.g. out-of-roundness (OOR), hole oversize (HOS) and conicity (CC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation